Reasons for and Reservations about Research Participation in Acutely Injured Adults - Irani, Elliane (J Nurs Scholarsh, 2015)
PURPOSE: The purpose of this study was to explore the reasons adult patients seeking emergency department care for minor injuries agree to participate in clinical research and to identify their reservations about participating in a research study. DESIGN AND METHODS: This is a secondary analysis of data from a longitudinal cohort study of 275 adults who sought emergency department care for physical injury and were followed over 12 months. At the final interview, participants were asked open-ended short-answer questions about their perception of participating in the study. Free text responses were analyzed using conventional content analysis. FINDINGS: The final sample of 214 participants was equally males and females, predominately Black (54%) and White (42%), with a mean age of 41 years. Six themes about reasons for participation emerged from free text responses: being asked, altruism, potential for personal benefit, financial gain, curiosity, and valuing and/or knowledge of research. Most did not report reservations. Those reservations identified included: time constraints, confidentiality, and whether patients felt well suited to fulfill the study requirements. CONCLUSION: Although injured patients are identified by the research community as vulnerable, they are willing to participate in research studies for diverse reasons and their participation is commonly associated with positive experiences.